Application of dual active bridge DC-DC converter in solid state transformer - Mohammad Tauquir Iqbal (Nanyang Technological University, 2022)
The global warming, depletion of non-renewable energy, and price reduction of renewable energy generation has led to the rapid rise in the researchers and industries interest towards more reliable electricity transmission. The distributed generators and energy storage cannot be integrated into the system in the presence of a conventional transformer due to the unavailability of a low voltage direct current (LVDC) link. A new intelligent transformer made up of the power electronics converter can mitigate the aforesaid problem associated with the conventional transformer. Moreover, SST has lesser size and weight than the conventional transformer due to a medium frequency transformer and provides current and voltage regulation, current limiting, energy storage management, and reactive power demand. SST is also used in electric traction, wind energy interfacing, or power quality improvement. The input of an SST is MVAC (medium voltage alternating current), while the output port is LVAC (low voltage alternating current). There are four kinds of architectures to implement a solid-state transformer; single-stage MVAC-LVAC conversion, two-stage MVAC-MVDC-LVAC conversion, two-stage MVAC-LVDC-LVAC conversion, and three-stage MVAC-MVDC-LVDC-LVAC conversion. The three-stage kinds of SST are most popular and architecture due to better and wide characteristics than the other three. The intermediate stage of a three-stage SST has an MVDC-LVDC converter. The converter needs to provide isolation between the input and output side, high-step down capability, bidirectional power, high current, soft-switching of the semiconductor devices. The dual active bridge (DAB) converter is the most suitable for the isolated bidirectional dc-dc converter in the intermediate stage of the SST. DAB converter offers low passive components, fixed-frequency operation, simple control methods, ZVS turn on, etc. Different modulation can increase its performance like low RMS current, reactive power minimization, extended ZVS range. The existing method for expressing the circuit current, voltage, and power is based on the circuit averaging technique. The expression is established by averaging the current over a time period of the circuit. Moreover, the RMS current is calculated from the time domain analysis of the inductor current. When operated as a variable duty cycle plus phase shift, there are nine modes of operation. In each mode of operation, the circuit behavior is different. The existing method of calculating the current, power, ZVS range of a DAB converter is to analyze the same circuit with different equations one by one. A Fourier series-based methodology for the DAB converter is proposed, eliminating the problem of solving the equation in each mode. The Fourier series approach is a unified solution to the state equation, current, voltage, power, and RMS current. This approach can be used in any type of DAB converter like T-type DAB, Semi-Dual DAB, Dual Transformer based DAB. The same procedure is later extended to a three-phase DAB converter. The standard methodology to obtain the model of a power electronic converter is achieved by averaging the state-space dynamics of the converter state variables. But the average of the transformer current is null over a switching cycle in the resonant dc-dc converter. Therefore, the conventional method is not well suited for resonant converters, including the bidirectional DAB converter. The two-time scale discrete-type models can resolve the problem associated with the standard state-space averaging methodology. The time-scale segregates the dynamics of the DAB converter into fast and slow state variables, which can be modeled separately and eases the analysis of the DAB converter. The effect of the core-loss of the inductor, dead-time of the semiconductor devices, output filter capacitor's equivalent series resistance, semiconductor on-resistance, and the transformer copper loss components are included in the model to improve its steady-state and dynamics characteristics. Moreover, the stability analysis using a bifurcation diagram is carried out of the digitally controlled closed-loop of the system. Furthermore, the critical gain for the stable region with variations in the circuit parameters like load resistance, circuit equivalent inductance, and voltage demand is extensively studied. The modeling and stability analysis is validated in the simulation and experimental setup. The proposed method accurately predicts the stable region with variations in the system circuit parameters. Thus this study provides a guide to select and tune the controller parameter to ensure the converter operates within the boundaries of the stable region. The discrete-time model of a DAB converter contains matrix exponential, which is approximated to first-order or second-order. The first-order approximation model gives an inaccurate model. Therefore, a second-order approximation of the matrix exponential is preferred. A novel first-order approximate of the matrix exponential-based bilinear discrete-time model is proposed to model a DAB converter. The same model can be used for the large and small-signal model of the system as well as for the stability analysis. An improved bilinear approximation is based on the evaluation of the matrix exponential with the help of linear algebra (using Eigenvalue and Eigenvector).